G139(P) The boy with the disappearing bones. (May 2019) - Furness, L; Riley, P; Briggs, T
Abstract : Introduction: Multicentric carpotarsal osteolysis (MCTO) is a rare monogenic skeletal dysplasia resulting in demineralization and osteolysis mainly affecting the carpal and tarsal bones and is mimic of Juvenile Idiopathic Arthritis (JIA). MCTO is associated with progressive nephropathy leading to Chronic Renal Failure and corneal clouding. De novo and familial heterozygous mutations of the gene MAFB are described as causative of MCTO. Case: We describe a 13 year old boy, born to non-consanguineous Caucasian parents who presented as an infant with joint pain and swelling and was diagnosed with Polyarticular JIA. Due to disease severity his treatment was quickly escalated; some resolution was described with Methotrexate and Adalimumab. Age 12 he was started on Tocilizumab due to disease flare despite joint injections. Further imaging showed carpal bone degeneration. Genetic testing identified a de novo heterozygous mutation in MAFB consistent with a diagnosis of MCTO. Ophthalmology review identified corneal clouding and a unilateral cataract. Renal function at age 13 years was normal. The patient has a diagnosis of Asperger's syndrome and had a skin lesion removed from the right 5th digit, containing calcium and phosphate. Discussion: In cases of diagnostic uncertainty or refractory disease such as this, further imaging and genetic testing plays a crucial role in establishing the aetiology, to guide targeted screening and appropriate genetic counselling. Through screening corneal clouding was identified. The finding of a cataract may relate to steroid use, but we note that MAFB is a transcription factor expressed in the eye and thus a role in cataract development could be postulated, although has not been described before. Whilst our proband shows no signs of renal disease, we note that this has been reported to present later in life and we will maintain follow up. The skin lesion observed is of interest and this has not, to our knowledge, previously been described in MCTO. The MCTO diagnosis raises important treatment questions. Whilst immunotherapy has not been shown to halt disease progression, a reduction in pain has been described. Through increased understanding of the functional mechanism by which MAFB results in bone destruction, it is hoped that targeted therapies, possibly through rankL may be developed.